Assessing information interaction to improve library ebook collections and services. Issue 2 (3rd April 2019) - Miller, Erin DeWitt; Rodriguez, Allyson; Smith, Susan
Abstract: That university students encounter issues and experience frustration when using ebooks is well documented, but more research into the specific issues they encounter is needed. This study focused on how successfully undergraduate and graduate students use ebooks and whether there are measurable differences between the two groups. Researchers employed user testing methodologies, including task analysis and talk aloud protocol, to research student interaction with the content and structure of ebooks on two platforms: ProQuest Ebook Central and EBSCO eBooks. Findings include suggested improvements for ebook platforms, considerations for collection development librarians, and areas of focus for library instructors.